USE OF FOREIGN LANGUAGE ONLINE TRAINERS FOR FORMING A FOREIGN LEXICAL COMPETENCE OF A FUTURE PEDAGOGUE - Solomakha, Angelika (Educological discourse, 2019)
The article considers modern approaches and innovative means of development of the foreign language communicative competence of future teachers. The author emphasizes and substantiates the necessity of widespread usage of digital technologies in the process of modern students` foreign language training as a component of professional pedagogical competence. The usage of on-line resources contributes not only to the acquisition of a foreign language, at the same time it is also an example, according to the methodological point of view, and can be used in further pedagogical activities in foreign language classes in pre-school establishments and in foreign language lessons in the New Ukrainian School. After graduating the university modern bachelors will work with the children – representatives of Generation Z, so the ability to use digital means of teaching a foreign language is a demand of time, because modern children, born in the digital would, must be taught by digital means. This is their natural environment. World leading countries understand the necessity of preparing teachers with a high level of a formed digital competence. So, the task of the XXI century modern university, which trains future educators for professional activity, is to form their readiness to teach in the New Ukrainian School by such means that follow the demands of time and will allow to form the XXI Century Competences. The article states that mastering the foreign language lexical material and deepening the level of lexical skills and abilities formation of students-bachelors of the specialty 013 Primary education, 012 Preschool education have a great general and practical significance, because the word is the main component of foreign language communicative competence, and the dictionary on-line simulators, which the author uses in the discipline "Foreign Language and Teaching Methodology (the German language)", allow to intensify the learning process both in the classroom and during the students’ self-work.